MASS NUCLEIC ACID TESTING - VARLEY, Katherine Elena; MOORE, David Troy (2024)
A method of screening large populations of subjects for the presence of an RNA, such as RNA from a pathogen, is provided. The method combines sample pooling, targeted RT-PCR, the use of universal PCR primers, and massive parallel sequencing. The method is extremely sensitive, and if combined with whole genome sequencing confers extremely high specificity combined with high resilience to potential genetic variation in a pathogen. The method can be used to insert a unique "barcode," that identifies the specific sample (such as a sample from an individual patient), into the DNA produced from the RNA, which allows the DNA from many samples to be pooled for sequencing while still enabling the identification of any individual samples that test positive.